Environmentally independent histological markers of wool quality: a comparative study of Gentile di Puglia and Sarda breeds - Topputi, Rossana; Molina, Maria Gabriela; Ventriglia, Gianluca; Quiroz Valiente, Jorge; Ramirez Guillermo, Miguel Angel; Bruno, Silvia; Ciani, Elena; Guerra, Lorenzo; Cesarani, Alberto; Landi, Vincenzo; Martinello, Tiziana (Frontiers in Animal Science, 2026)
Wool quality plays a role in determining the economic value of sheep breeds, amid the growing global demand for natural and sustainable material. This quality depends on both genetic and non-genetic factors, complicating breed evaluation. Among the most valued qualities is the fine wool produced by Merino and Merino-derived breeds. This study aims to identify parameters measured under controlled environmental conditions to assess the degree of merinization within flocks, meaning the extent to which a breed exhibits morphological and histological traits typical of Merino sheep. The ancient Italian sheep breed, Gentile di Puglia, derived from Merino, was compared with the non-merinized Sarda breed. Our results demonstrate that follicular structure is a key indicator for assessing merinization, under standardized environmental conditions and across different age groups. Gentile di Puglia sheep exhibited significantly higher secondary follicle density and secondary-to-primary follicle ratio (S/P = 8,96 vs 2,29) compared to the Sarda breed, indicating a finer wool structure. The density of sebaceous glands was significantly higher in the adult Gentile di Puglia, and no significant differences in gland area were found between breeds. These results highlight the importance of sebaceous glands in lanolin production and provide objective criteria for evaluating wool quality. This supports the promotion of the Gentile di Puglia breed for sustainable wool production. These results provide a novel phenotypic characterization at the histological level, that could guide future genomic studies aimed at identifying the genes responsible for these traits, relevant for the conservation and sustainable use of these local breeds. These findings not only provide a reliable histological basis for assessing wool quality but also offer practical markers that can inform selective breeding programs aimed at enhancing merino-like traits in local sheep populations.